Associations between stressful life events and diabetes: Findings from the China Kadoorie Biobank study of 500,000 adults - Wang, M; Gong, W; Hu, R; Pan, J; Lv, J; Guo, Y; Zheng, B; Chen, Z; Li, L; Zhong, J (Wiley, 2019)
Aims/Introduction Evidence has shown that stressful life events are associated with the development of diabetes, yet studies in mainland China are scarce. In the present study, we explored the associations between cumulative and specific stressful life events and the prevalence of diabetes in Chinese adults. Materials and Methods The cross‐sectional data were from the China Kadoorie Biobank study, which enrolled approximately 500,000 adults aged 30–79 years from 10 diverse regions of China. Logistic regression models were used to calculate the adjusted odds ratio (OR) and the 95% confidence interval (CI). Results Of the 473,607 participants, 25,301 (5.34%) had type 2 diabetes (2.68% clinically‐identified and 2.66% screen‐detected). Participants who experienced one and two or more stressful life events were 1.10‐fold (OR 1.10, 95% CI 1.05–1.16) and 1.33‐fold (OR 1.33, 95% CI 1.13–1.57) more likely to have type 2 diabetes. Three categories of work‐related events (OR 1.15, 95% CI 1.01–1.31), as well as family‐related events (OR 1.11, 95% CI 1.06–1.18) and personal‐related events (OR 1.18, 95% CI 1.03–1.36), were associated with an increased likelihood of type 2 diabetes. Regarding the specific life events, the ORs of loss of job or retirement, as well as major conflict within family, death or major illness of other close family member and major injury or traffic accident, were 1.24 (95% CI 1.02–1.52), 1.24 (95% CI 1.08–1.43), 1.13 (95% CI 1.06–1.20) and 1.20 (95% CI 1.01–1.43), respectively. Conclusions The present study showed that cumulative and specific stressful life events were significantly associated with an increased prevalence of diabetes.